A role for copper in protozoan grazing – two billion years selecting for bacterial copper resistance. Issue 4 (31st August 2016) - Hao, Xiuli; Lüthje, Freja; Rønn, Regin; German, Nadezhda A.; Li, Xuanji; Huang, Fuyi; Kisaka, Javan; Huffman, David; Alwathnani, Hend A.; Zhu, Yong‐Guan; Rensing, Christopher
Summary: The Great Oxidation Event resulted in integration of soft metals in a wide range of biochemical processes including, in our opinion, killing of bacteria by protozoa. Compared to pressure from anthropologic copper contamination, little is known on impacts of protozoan predation on maintenance of copper resistance determinants in bacteria. To evaluate the role of copper and other soft metals in predatory mechanisms of protozoa, we examined survival of bacteria mutated in different transition metal efflux or uptake systems in the social amoeba Dictyostelium discoideum . Our data demonstrated a strong correlation between the presence of copper/zinc efflux as well as iron/manganese uptake, and bacterial survival in amoebae. The growth of protozoa, in turn, was dependent on bacterial copper sensitivity. The phagocytosis of bacteria induced upregulation of Dictyostelium genes encoding the copper uptake transporter p80 and a triad of Cu(I)‐translocating PIB ‐type ATPases. Accumulated Cu(I) in Dictyostelium was monitored using a copper biosensor bacterial strain. Altogether, our data demonstrate that Cu(I) is ultimately involved in protozoan predation of bacteria, supporting our hypothesis that protozoan grazing selected for the presence of copper resistance determinants for about two billion years. Abstract : Protozoans are ubiquitous bacterial predators and pathogen reservoirs. We have characterized the protozoan use of copper as an efficient weapon during predation. Thus copper poisoning imposes a selective pressure upon copper resistance determinants in bacteria.